The development of novel theranostic agents for breast cancer imaging and treatment - Duthoit, Sophie (2021)
Cancer is a disease that affects up to one in two people [1]. There are currently a wide variety of treatment options available but these are limited by toxic side effects such as myelosuppression and alopecia [2]. One new treatment option being developed is theranostics. Theranostics is a technique that combines therapeutic and diagnostic components, and is increasingly of interest in the field of oncology.